Sequence identification and description of the mitochondrial genome of Abbottina rivularis (Cypriniformes: Cyprinidae). (3rd March 2016) - Wang, Heng; Yang, Xiaoxue; Wang, Xiarong; Li, Chen; Gu, Jiangwen; Yang, Shoubao; He, Liping; Lv, Sisi; Huang, Pingping
Abstract: In this study, the complete mitochondrial genome of Abbottina rivularis was determined; the phylogenetic analysis with other individuals and closely related species of the gudgeons was carried out. The complete mitogenome of A. rivularis was 16, 597 bp in length, which consists of 22 tRNA genes, 13 protein-coding genes, 2 rRNA genes, and 2 non-coding regions: (D-loop and OL). The overall nucleotide composition of the A. rivularis mitogenome was A: 29.92%, T: 25.75%, G: 17.15% and C: 27.18%, respectively, with an A + T rich feature (57.1%). This study provides useful data to genetics, conservation and evolution study of the gudgeons.